Codonopsis atriplicifolia (Campanulaceae), a new species from western Sichuan, China - Zhou, Yu-Yang; Si, Yun-Hao; Zhang, Zhen; Wang, Qiang; Yu, Yan (Phytotaxa, 2021)
Codonopsis atriplicifolia (Campanulaceae) from western Sichuan, China, is described here as a new species, which is similar to C. subscaposa in a number of characters. The results of molecular phylogenetic analysis of 25 species of Codonopsis based on chloroplast DNA fragments (matK, petD with petB-petD, rbcL) show that C. atriplicifolia is closely related to C. farreri. In morphology, the new species is distinctly different from the allied species by its linear-lanceolate leaves with subentire to pinnatipartite margins.